Analisis Pesan Dakwah Toleransi Di Akun Instagram Berbeda Tapi Bersama Episode 8 - Putri Isma Indriyani (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah UIN Sultan Maulana Hasanuddin Banten, 2022)
Instagram itself becomes the most popular medium and becomes the wah media for the da 'i and the da 'iah to deliver their preaching. By uploading or veiling islamic content with such a creative and attractive presentation of the people that islamic up-and-forth activities in predating the media will be popular and a trend in society to continue spreading the preaching. The tolerance dakwah message analysis on the instagram account is different, but together it comes with a semiotical analysis method of Charles sanders Pierce. In order to know the process of symbols found in videos when talking religion with a relaxed atmosphere on a different theme but with episode 8. Tolerance is mutual respect for one another despite differing viewpoints.